Chronic pain in female breast cancer survivors - prevalence, characteristics and contributing factors: a cross-sectional pilot study - Nelisiwe Shabangu; Tselane Thebe; Michelle Casey; Ursula Wesselmann; Romy Parker (BMC, 2023)
Abstract Background While the global incidence of breast cancer is increasing, there is also an increase in the numbers of breast cancer survivors and in survival duration, as early detection programs are implemented, and treatments are optimized. Breast cancer survivors in several countries commonly struggle with a range of symptoms (fatigue, insomnia, depression) with 25-80% of survivors suffering from chronic pain. There is a paucity of literature reporting on breast cancer survivors in South Africa. In this pilot study we aimed to determine the prevalence of chronic pain in female breast cancer survivors attending the breast oncology clinic. Methods A cross-sectional survey was conducted of all breast cancer survivors attending the Groote Schuur Hospital Breast Unit during one month in 2019. 44 female breast cancer survivors (median age 60.5y) completed a sociodemographic questionnaire, the Brief Pain Inventory, Pain Catastrophizing Scale and measures for neuropathic pain (DN4), health related quality of life (HRQoL; EQ-5d-3 L), physical activity (IPAQ), depression and anxiety (PHQ4), and screening questions to evaluate sleep, happiness and perceived discrimination in the language of their choice. Results The prevalence of chronic pain (pain on most days for more than three months) was 59% (95%CI 44-72), a significantly higher number than the 18,3% prevalence of chronic pain reported by South African adults. 39% of the women were classified as having neuropathic pain. The median pain severity score was 3.75 (IQR = 2.75-5) and the median pain interference with function score was 4 (IQR = 2.9-5.4). The women were experiencing pain in a median of 2 different body sites (IQR = 1-3). The women with pain were more likely to be unemployed or receiving a disability grant, had significantly worse HRQoL, and significantly worse scores for risk of depression and anxiety. Conclusion The results of this pilot study suggest that chronic pain may be a significant burden for South African breast cancer survivors. Routine screening for chronic pain in breast cancer survivors is recommended with a larger study indicated to explore this issue further.